Analisis Pengelolaan Dana Desa Pada Lembang Rinding Kila Kecamatan Buntao Kabupaten Toraja Utara - Grace Yugo Paerong; Dina Ramba (Jurnal Ekonomi dan Pembangunan Indonesia, 2023)
Analysis of Village Fund Management in Lembang Rinding Kila’ Buntao’ District, Toraja Utara Regency. Supervised by Dra Dina Ramba, MM and Jens Batara Marewa, MM. This study aims to find out how the use of the Village Fund is carried out by the Government and whether it is in accordance with existing procedures and has a clear direction towards village development. The mothed used is an interview, documentation, and observation with the head of Lembang Rinding Kila’ about the Management of Village Funds in 2020 and 2021 which includes the annual village income and what income comes In.The result achieved is that the Village Fund Management in Lembang Rinding Kila’ is already effective, because Lembang Lembang’s inventory fund, so it has complied with Permendagri Regulation Number 113 of 2014 concering Village Fund Management.